POLITICAL PARTICIPATION AND TRUST OF YOUTH IN SERBIA AND THE REPUBLIC OF SRPSKA IN POLITICAL INSTITUTIONS - Vuković, Đorđe; Vranješ, Aleksandar; Radanović, Srđan (Politeia, 2025)
This paper examines the level of political trust and patterns of political participation among young people in Serbia and the Republic of Srpska, focusing on members of Generation Z. Using a mixed-method approach and a sample of 555 respondents, the study analyzes key dimensions of political culture, including media literacy, political involvement, cynicism, anomie, institutional trust, authoritarian tendencies, and attitudes toward national symbols. The findings reveal a strikingly low level of trust in essential political institutions—government, parliament, presidency, judiciary, and political parties—despite a relatively high rate of electoral participation. Most young people believe that political parties do not represent citizens’ interests, that media are not reliable sources of information, and that individuals have no real possibility to influence political decision-making. Although Generation Z shows strong attachment to national symbols and displays tolerance toward diversity, there is a growing sense of political cynicism, marginalization, and dissatisfaction with traditional democratic institutions for failing to meet the expectations of young people. The results point to a structural crisis of political legitimacy and emphasize the need for new mechanisms to meaningfully integrate young people into political processes. Strengthening the institutional trust of Generation Z emerges as a key prerequisite for democratic consolidation.
Keywords: Political participation; social networks; youth; Generation Z; trust; institutions; Serbia; Republic of Srpska